Establishment of latency in mice by herpes simplex virus 1 recombinants that carry insertions affecting regulation of the thymidine kinase gene. - Sears, A E (1985)
Herpes simplex virus 1 recombinants carrying alpha-, beta-, and late gamma (gamma 2)-regulated thymidine kinase (TK) genes were tested for the ability to establish latency in BALB/c mice inoculated by the eye route. The significant findings were as follows. Representatives of alpha- and gamma 2-regulated TK recombinants all established and maintained latent infections, but the efficiency was somewhat lower than that of wild-type virus. Of the three alpha TK recombinants tested, one (R316) spontaneously deleted portions of the inserted sequences which conferred alpha regulation to the TK gene. The viruses carrying these deletions expressed considerably lower TK activity than did wild-type virus, i.e., 2 to 40% of the levels expressed by the wild-type virus carrying the beta TK gene. However, the ability of these viruses to establish latency was not related to the efficiency of expression of the TK gene. These results indicate the following: (i) conversion of the TK gene into an alpha or gamma 2 gene did not preclude the establishment of latent infections; (ii) there was no correlation between the levels of TK activity expressed in cell culture and the ability to establish latency; and (iii) rearrangement of the genome by insertions or deletions which interrupt gene domains did not automatically result in an inability to establish latent infections.